Comparative aerodynamic analysis of commercial swimsuits - Hazim, M.; Harun, C.; Firoz, A.; Aleksandar, S. (Sports Technology, 2010)
The primary objective of this research is to investigate and describe the effects of swimsuits' surface profile and seam orientations on aerodynamic drag. Two commercial swimsuits (Speedo LZR and TYR Sayonara) materials were evaluated in a wind tunnel environment using a standard cylindrical experimental arrangement. The effects of swimsuit surface profile and seam orientations on aerodynamic drag were evaluated for a range of Reynolds numbers. The measured drag forces were converted to dimensionless drag coefficients, which were compared for both swimsuits under different conditions. The results show that the material surface structure (roughness and seam orientations) of the swimsuit has significant effect on aerodynamic drag. The seam orientation at 45Â° has the potential to reduce the drag by around 15% depending on the seam geometry (i.e., seam height, width, etc.) and Reynolds number. The TYR Sayonara swimsuit can provide aerodynamic advantage at low Reynolds number (e.g. below Re = 1.63 x 10^5) due to lower CD value. The Speedo LZR swimsuit has relative advantage at high Reynolds number (e.g. over Re = 1.63 x 10^5) compared to TYR Sayonara swimsuit as it has significantly lower CD values at high Reynolds number.